2011
DOI: 10.1016/j.bbmt.2010.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Donor Serostatus Has an Impact on Cytomegalovirus-Specific Immunity, Cytomegaloviral Disease Incidence, and Survival in Seropositive Hematopoietic Cell Transplant Recipients

Abstract: More cytomegalovirus (CMV)-specific T cells are transferred with grafts from CMV seropositive than seronegative donors. We hypothesized that seropositive recipients of grafts from seropositive donors (D+R+) have higher counts of CMV-specific T cells than seropositive recipients of grafts from seronegative donors (D-R+), and that this is clinically relevant in the setting of in vivo T cell depletion using rabbit-antihuman thymocyte globulin (ATG). We reviewed charts of 298 ATG-conditioned, seropositive recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
37
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 50 publications
7
37
0
2
Order By: Relevance
“…The present results are consistent with reports from other transplant settings, in particular when ATG is administered as GvHD prophylaxis and when the donor is CMV seronegative; [11][12][13] similarly, the profound state of immune suppression here prevents or impairs the prompt recovery of anti-CMV immunity, this latter recently associated with a better protection from overall infections in the context of haplo-HSCT with PT-Cy. 14 Abbreviations: BM = bone marrow; HCT-CI = hematopoietic cell transplantation-specific comorbidity index; MAC = myeloablative conditioning; MDS = myelodisplastic syndrome; MPS = myeloproliferative syndrome; NMA = nonmyeloablative; RIC = reduced-intensity conditioning.…”
supporting
confidence: 81%
“…The present results are consistent with reports from other transplant settings, in particular when ATG is administered as GvHD prophylaxis and when the donor is CMV seronegative; [11][12][13] similarly, the profound state of immune suppression here prevents or impairs the prompt recovery of anti-CMV immunity, this latter recently associated with a better protection from overall infections in the context of haplo-HSCT with PT-Cy. 14 Abbreviations: BM = bone marrow; HCT-CI = hematopoietic cell transplantation-specific comorbidity index; MAC = myeloablative conditioning; MDS = myelodisplastic syndrome; MPS = myeloproliferative syndrome; NMA = nonmyeloablative; RIC = reduced-intensity conditioning.…”
supporting
confidence: 81%
“…4 Furthermore, 60% of the cohort underwent myeloablative conditioning. Interestingly, our assertion that strategies that result in full donor chimerism might offer little antiviral protection in the context of R1/D2 transplants is supported by the clinical outcome data of these studies, 4,5 as well as by a smaller study that demonstrated persistence of recipient-derived CMV-specific T cells in T-deplete but not T-replete HSCT. 12 The latter study used an in vitro T-cell depletion strategy with Campath-1M plus complement, which results in depletion of mainly donor T cells while leaving recipient T cells intact.…”
Section: Discussionsupporting
confidence: 56%
“…This may explain the apparent discrepancy between our results and those in a large group of patients undergoing HSCT incorporating antithymocyte globulin. 5 Although reconstitution of CMV-specific T-cell immunity was slower in those with CMV seronegative donors, with a coincident increase in CMVrelated complications, almost 50% of the cohort developed clinically significant GvHD, and chimerism was fully donor in all evaluable R1/D2 patients by 3 months post-HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the D-/R+ LTx patients included in this analysis developed CMV disease and only 5.9% developed CMV infection. The marked difference in the observed rates of CMV infection or disease between D-/R+ and D+/R+ patient may be related to R+ LTx patients having only partial immunity to the CMV strain carried by the D+ organ (17). Whereas recipients of D-organs have preexisting T cell-specific immunity to protect against reactivation of their native CMV strain, many recipients of D+ organs may require several months to develop T cell-specific immunity that confers protection against CMV superinfection by the donor strain.…”
Section: Discussionmentioning
confidence: 99%